Effect of Cu and Sm doping on the ferroelectric character of bismuth ferrite thin films. (4th March 2022) - Sathiya Priya, A.; Geetha, D.; Henry, J.
Abstract: This report discusses the effect of substitution of copper (Cu) and samarium (Sm) at the Fe-site and Bi site respectively on structural, morphological, optical and ferroelectric properties of bismuth ferrite (BiFeO3 ) films. Pure and (Sm, Cu) co-doped perovskite BiFeO3 thin films were fabricated on fluorine doped tin oxide substrates by sol–gel assisted spin coating technique. The X-ray diffraction analysis revealed the rhombohedral structure of all the samples. This confirmed that no phase change occurred due to doping. The atomic force microscopy (AFM) images of the films present uniform distribution of grains. The UV–Vis spectra demonstrated increased absorption for the doped samples. The corresponding Tauc plots exposed reduction in the energy bandgap of the doped films. The ferroelectric studies exhibited significantly improved saturation polarization, remnant polarization and coercive field of the doped films. The reduced band gap in the visible region and enhanced ferroelectric behavior of (Sm, Cu) co-doped bismuth ferrite films favor their suitability in visible light photovoltaic applications. GRAPHICAL ABSTRACT: UF0001